Handbook of critical theory - Rasmussen, David M. (Blackwell Publishers, 1996)
The Handbook of Critical Theory brings together for the first time a detailed examination of the state of critical theory today. The sixteen essays provide analyses of the various orientations that critical theory has taken both historically and systematically in recent years, expositions of the new perspectives that have begun to shape the field, and reflections upon the direction of critical theory.